EVALUASI TINGKAT SANITASI, TOTAL MIKROBA DAN E. coli PADA PERALATAN MAKAN KANTIN SEKOLAH - Suyanto, Agus; Nurrahman, Nurrahman; Najmatul Laila, Nadia (Jurnal Pangan dan Gizi, 2024)
The canteen is one of the public infrastructures that functions as a place to sell food and drinks for students and school teachers. This study aims to evaluate the level of sanitation of school canteens with indicators of total microbes and Escherichia coli found on plates, glasses, and spoons and total microbes in the canteen air. The evaluation was carried out by comparing data before and after coaching canteen traders, including testing total microbe samples, namely Total Plate Count (TPC), E. coli testing, and testing the level of sanitation using the Good Processed Food Production Method (CPPOB) form. The results of the statistical test did not affect the total microbes of equipment and air but did affect the reduction of E. coli and the level of sanitation of the school canteen.